1996
DOI: 10.1128/iai.64.9.3946-3949.1996
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the antigranulocyte monoclonal antibody RB6-8C5 impairs resistance of mice to gastrointestinal infection with Listeria monocytogenes

Abstract: Treatment with the antigranulocyte monoclonal antibody (MAb) RB6-8C5 increased the severity of infection in mice intragastrically inoculated with Listeria monocytogenes. Most MAb RB6-8C5-treated mice died when inoculated intragastrically with as few as 4 ؋ 10 4 L. monocytogenes bacteria, whereas most control mice survived intragastric inoculation with 4 ؋ 10 8 L. monocytogenes bacteria. The increased severity of infection in MAb RB6-8C5-treated mice appeared to result from listerial multiplication in the splee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…idly controlled, requiring the use of immunosuppression by polymorphonuclear depletion (Czuprynski et al, 1996) to induce a continuous bacterial growth in the bone marrow and CNS infection (data not shown). Therefore we used the intravenous model of acute listeriosis, allowing the determination of phenotypes of bone marrow and blood infected cells during the induction of a reproducible CNS invasion.…”
Section: Bone Marrow Infection During Listeriosissupporting
confidence: 93%
“…idly controlled, requiring the use of immunosuppression by polymorphonuclear depletion (Czuprynski et al, 1996) to induce a continuous bacterial growth in the bone marrow and CNS infection (data not shown). Therefore we used the intravenous model of acute listeriosis, allowing the determination of phenotypes of bone marrow and blood infected cells during the induction of a reproducible CNS invasion.…”
Section: Bone Marrow Infection During Listeriosissupporting
confidence: 93%
“…Although L. monocytogenes bacteria can induce systemic infection causing spontaneous abortion, septicemia, and meningitis, anti-L. monocytogenes immunity in humans has not been defined. In murine models of systemic L. monocytogenes infection, mice deficient in neutrophils exhibit increased bacterial burden during early L. monocytogenes infection (14)(15)(16). In addition, murine IFN-g, IL-23, IL-17, and CD8 + T cells have been shown to play a role in protection against L. monocytogenes infection (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Other studies suggested that preventing gastric acidity or emulsifying the L, monocytogenes inoculum in a food product can enhance the severity of infection (19)(20). Usually there is httle sign of local invasion or multiplication of L, monocytogenes in the intestinal mucosa (21)(22). Bacteriological and histopathological analyses have documented invasion via Peyer's patches or intestinal epithelial cells (16,21).…”
Section: Experimental Gastrointestinal Infection With L Monocytogenesmentioning
confidence: 99%
“…Even when high challenge doses are used successfully to initiate systemic infection, there are usually few or no lesions in the intestinal mucosa (21,22,103). In addition, L. monocytogenes is rapidly diluted in the intestinal tract and is difficult to recover from intestinal contents more than a few days after g.i.…”
Section: Fig I a Simphbed Illustration Ofthe Hopelessly Complex Intmentioning
confidence: 99%
See 1 more Smart Citation